The influence of family socio-economic status on learning engagement of college students majoring in preschool education: The mediating role of parental autonomy support and the moderating effect of psychological capital - Qiu, Yuan; Ye, Pingzhi (Frontiers in Psychology, 2023)
This study constructs a moderated mediation model to explore the relationship and mechanism between family socio-economic status and learning engagement of college students majoring in preschool education. The mediating effect of parental autonomy support and the moderating effect of psychological capital were also investigated. Through the questionnaire survey of 986 participants, it was found that family socio-economic status has a significant direct effect on learning engagement. In addition, parental autonomy support has a complete mediating effect between family socio-economic status and learning engagement. Besides, psychological capital has a significant positive moderating effect on the relationship between parental autonomy support and learning engagement. Finally, according to the research results, this study puts forward feasible education suggestions from two aspects of family and school.